Aerobic potential, stroke parameters, and coordination in swimming front-crawl performance - Pelayo, P.; Alberty, M.; Sidney, M.; Potdevin, F.; Dekerle, J. (International Journal of Sports Physiology and Performance, 2007)
The purposes of this review were (1) to review the recent studies conducted in swimming on the assessment of aerobic potential and establishment of exercise-intensity domains (it is important that exercise-intensity domains be accurately defined and their physiological underpinnings well understood to optimize and evaluate training programs); (2) to analyze changes in traditionally measured stroke rate and stroke length during exhaustive swims, particularly in relation to the predetermined intensity domains (introduction of an "optimal swimming technique speed"); and (3) to introduce the latest swimming research on arm coordination that might help us better understand the technical adaptations of swimmers under physical stress.